(untitled) (San Francisco, 2003)
Kurzweil offers a wide range of Jewish writing by 56 authors on the subjects of Israel, current issues, religious education and practice, Jewish spiritual thought, kabbalah, the Holocaust, and anti-Semitism--in the form of poetry, fiction, and humor. In this third annual volume of the best Jewish writing of the past year, Kurzweil stresses the importance of presenting diverse points of view and topics that are particularly timely. To that end, the contributors include such well-known writers as Elie Wiesel, Amos Elon, Herbert Gold, David Grossman, Cynthia Ozick, Marge Piercy, Arthur Waskow, Arthur Hertzberg, and Adin Steinsaltz. Wiesel's piece is a letter to President Bush on the day that Israeli prime minister Ariel Sharon was meeting with Bush; Elon and Grossman examine the Israeli-Palestinian conflict; and Ozick's article on kabbalah concerns the mythic passions of Gershom Scholem. Piercy's poem speaks of the solace of Rosh Hashanah, and Waskow discusses an Israeli soldier's refusal to serve in the occupation army. Like the two previous volumes, this one is provocative and highly relevant. George Cohen
Keywords: American literature,Judaism,American literature,Văn học Mỹ,Do Thái giáo,Văn học Mỹ; Jewish authors,Tác giả Do Thái; 20th century,Thế kỷ 20